(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Plastic bottles are constructed from high-density plastic. Plastic bottles are now one of the top problems not only in the country but also worldwide. Plastic bottles are a huge barrier to the canals because it causes flooding. Thus, the researchers had an idea to make an eco-friendly chair by using plastic bottles. The purpose of this research was to teach people how to manage their waste properly and help them to create eco-friendly chairs by using recyclable plastic bottles. This study showed how our waste plastic bottles turn into useful things that can help the community and the school. The researchers recommend that every student can create a valuable product similar to an eco-friendly chair. It can make someone more creative, and it turns into a business. It can also improve the discipline of the students in Bestlink College of the Philippines. The research method used was the descriptive method, which was suitable for this study. The descriptive study determines and reports the way things are. The study comprised all students that presented facts regarding the nature and status of anything. This study was concerned with the circumstances of the relationship. The results of the study strongly agreed that making an eco-friendly chair by using waste plastic bottles is effective because it turns plastic bottles into useful things in our community and helps the students to be more creative and disciplined. This study discussed the importance of being disciplined to the students, which was the main purpose of this study.